Factor structure of physical efficiency in female judo competitors at various stages of long-standing training - Wolska, B.; Jagiello, W.; Smulskij, W. (Archives of Budo, 2010)
The main aim of the study is to determine a factor structure of the state of systems of energy provision for effort of judo athletes at various stages of long-standing training. In each group four factors determining the structure of the system of energy provision for the athletes' effort were identified, and their most informative indices were determined.